Mathematics Addendum - class 3 - Iranga Galhenage,Don Celsus Shenal; Nosheen Hsaan; Siddiqua Maqsood (Ideal furnishers, 2022)
The Mathematics Addendum for Class 3 enhances the curriculum by focusing on essential concepts such as numbers and place value, addition and subtraction, multiplication and division, fractions, measurement, geometry, and data handling. It introduces students to three-digit numbers, various strategies for arithmetic operations, and the basics of fractions and measurements. The addendum incorporates hands-on activities, math games, and practice worksheets, along with real-world applications to reinforce learning. By providing diverse resources and engaging methods, the addendum aims to deepen students' understanding and appreciation of mathematics.
This addendum aims to support Class 3 students in mastering fundamental math concepts through engaging and interactive methods. By using a variety of resources and activities, we hope to foster a deeper understanding and appreciation for mathematics.
Keywords: Place Value; Three-Digit Numbers